Synthesis, characterization and thermal decomposition of [Pd2 (C2-dmba) (μ-SO4) (μ-SO4) SO22] - Caires, Antonio Carlos Fávero; Mauro, Antonio Eduardo [UNESP] (FapUNIFESP (SciELO), 1998)
The bridged sulphate complex [Pd2 (C2,dmba) (μ-SO4) (SO2)2] has been obtained by reacting a saturated solution of SO2 in methanol and the cyclometallated compound [Pd(C2,N-dmba)(μ-N3)]2; (dmba = N,N-dimethylbenzylamine), at room temperature for 24 h. Reaction product was characterized by elemental analysis, NMR comprising 13C{1H} and 1H nuclei and I.R. spectrum's measurements. Thermal behavior has been investigated and residual products identified by X-ray powder diffraction.
Keywords: Azido-cyclopalladated; Reactivity; Sulphur dioxide; Thermal decomposition